King of Show-and-Tell - Klein, Abby (Scholastic, Inc, 2004)
Freddy Thresher doesn't mean to get in trouble.... It's just that he never has anything good for show-and-tell. This time, he's found something that's really exciting, but if his "Neat Freak" mother finds out, she'll be furious. How can Freddy sneak his secret "share" past his mom and bring it to school?